2017
DOI: 10.1002/mrm.27036
|View full text |Cite
|
Sign up to set email alerts
|

Placenta microstructure and microcirculation imaging with diffusion MRI

Abstract: PurposeTo assess which microstructural models best explain the diffusion‐weighted MRI signal in the human placenta.MethodsThe placentas of nine healthy pregnant subjects were scanned with a multishell, multidirectional diffusion protocol at 3T. A range of multicompartment biophysical models were fit to the data, and ranked using the Bayesian information criterion.ResultsAnisotropic extensions to the intravoxel incoherent motion model, which consider the effect of coherent orientation in both microvascular stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 50 publications
7
59
1
Order By: Relevance
“…Naturally, the product of this perfusion fraction with the pseudodiffusivity is a correlate of blood flow. Although the model fitting is prone to noise, several authors have attempted to make fitting more robust …”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…Naturally, the product of this perfusion fraction with the pseudodiffusivity is a correlate of blood flow. Although the model fitting is prone to noise, several authors have attempted to make fitting more robust …”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Diffusion measurements of this type can be enhanced by including directional sensitisation, and this has been used frequently in other organs to reveal the organisation of the tissue structure, especially the brain . In the placenta, the directional sensitivity might reveal information about the structure of the villous tree and how this changes in pathology such as FGR where insufficient spiral artery remodelling is thought to lead to mechanical damage and immaturity in the fetal villous tree which may reduce the measured diffusion of water.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has shown that anisotropy is present in both the perfusion (i.e low b-value) and diffusion (high b-value) placental dMRI signal components. 41 We therefore designed a bespoke diffusion weighted single shot EPI sequence. This has 3 gradient directions at b = 5, 10, 25, 50, 100, 200, 400, 600, 1200 and 1600 s/mm 2 , 8 directions at b = 18 s/mm 2 , 7 directions at b = 36 s/mm 2 , and 15 directions at b = 800 s/mm 2 , in addition 6 volumes at b = 0 s/mm 2 were acquired interspersed through the acquisition.…”
Section: Bespoke Multi-modal Mri Acquisitionmentioning
confidence: 99%